Ion-Exchange Based Immobilization of Chromogenic Reagents on Microfluidic Paper Analytical Devices - Rahbar, Mohammad; Wheeler, Aaron R; Paull, Brett; Macka, Mirek (Analytical chemistry, 2019)
Distance-based detection methods, as used in development of microfluidic paper analytical devices (μPADs), rely on the dynamic formation of a colored band along the length of the paper microfluidic channels. The color change is driven by the reaction of chromogenic reagents (typically water-insoluble) that are bound to the paper, thus not subject to being washed away by the sample flow along the detection channel. Here, we introduce the use of an anion-exchange filter paper (as a replacement for standard, unmodified filter paper) for distance-based detection in μPADs, in order to immobilize the water-soluble anionic reagents upon the paper detection channels based on ion-exchange interactions of the oppositely charged paper (protonated tertiary amine groups) and the anionic groups of the reagents. The ion-exchange (IE) paper was initially characterized and its properties were compared with standard cellulose paper. The IE paper was shown to be capable of strong retention of anionic reagents exhibiting acidic functional groups (carboxylic, sulfonic), which become deprotonated and negatively charged when in contact with the IE paper. The effect of the ionic strength (10-250 mM Cl-) and pH (1-13) on the immobilization of the investigated reagents were also determined. The IE-μPADs were then modified with anionic chromogenic reagents and applied to distance-based determination of total calcium (LOD = 0.03 mM) and total acidity (LOD = 2.5 mM) content in serum and wine samples, respectively. The detailed mechanisms of the developed assays on the IE paper are also discussed. We propose that IE-μPADs represent a useful new addition to the distance-based detection toolbox and considerably enhance the applicability of such a detection method.